ANALYSIS OF LEAF BLADE AREA AND TOTAL ILLUMINATION INDEXES OF PANICUM MAXIMUM JACQ. CV. ARIES GRASS WITH DIFFERENT NITROGEN RATES FOR SHEEP FEEDING - da Costa, L. P. R.; Moreira, A. L.; Gabriel Filho, L. R. A.; Souza, R. DE O.; Cremasco, C. P.; Putti, F. F.; Chacur, M. G. M. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Improvement of nutrition of small ruminants increases production and minimizes costs, especially during dry periods. On the other hand, investments in energy and protein foods cause high production costs. An economical alternative lies in investing in fodder production featuring quality and quantity, by lowering costs and maximizing profits of commercial farms. Current research analyzes forage of the pasture grass Panicum maximum Jacq. cv. Aries, fertilized with 200 and 400 kg of nitrogen per ha/year, and applying Student´s t test to compare the effects in pasture development. The best fertilization for quality forage production within the region´s climate and for sheep breeding was assessed. There were no significant differences among the different levels of nitrogen with regard to total illumination and leaf area index. Results show that the use of the least amount of fertilizer, i. e. 200 kg-1ha-1 year, is economically viable, taking into account lower costs in their acquisition, transportation and application.